Characterisation and antifungal activity of extracellular chitinase from a biocontrol fungus, Trichoderma asperellum PQ34 - Loc, Nguyen Hoang (Mycology, 2019)
Trichoderma species were known as biological control agents against phytopathogenic fungi because they produce a variety of chitinases. Chitinases are hydrolytic enzymes that break down glycosidic bonds in chitin, a major component of the cell walls of fungi. The present study shows that extracellular chitinase activity reached a maximum value of approximately 22 U/mL after 96 h of T. asperellum PQ34 strain culture. The optimal temperature and pH of enzyme are 40°C and 7, respectively, whereas the thermal and pH stability range from 25°C to 50°C and 4 to 10, respectively. Chitinase at 60 U/mL inhibited nearly completely in vitro growth of Colletotrichum sp. (about 95%) and Sclerotium rolfsii (about 97%). In peanut plants, 20 U/mL of chitinase significantly reduced the incidence of S. rolfsii infection compared to controls. The fungal infection incidence of seeds before germination and 30 days after germination was only 2.22% and 2.38%, while the control was 13.33% and 17.95%. Besides, chitinase from T. asperellum PQ34 can also prevent anthracnose that is caused by Colletotrichum sp. on both mango and chilli fruits up to 72 h after enzyme pre-treatment at 40 U/mL. In mango and chilli fruits infected with anthracnose, 40 U/mL dose of chitinase inhibited the growth of fungi after 96 h of treatment, the diameter of lesion was only 0.88 cm for mango and 1.45 cm for chilli, while the control was 1.67 cm and 2.85 cm, respectively.